2016
DOI: 10.26503/todigra.v2i3.56
|View full text |Cite
|
Sign up to set email alerts
|

Postdigital Interfaces and the Aesthetics of Recruitment

Abstract: This paper analyses reconfigurations of play in emergent digital materialities of game design. It extends recent work examining dimensions of hybridity in playful products by turning attention to interfaces, practicesand spaces, rather than devices. We argue that the concept of hybrid playrelies on predefining clear and distinct digital or material entities that then enter into hybrid situations. Drawing on concepts of the ‘interface’ and ‘postdigital’, we argue the distribution of computing devices creates di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Although play was significant for all early years settings that participated in the MakEY project, it was evident that the nature of play is changing in a world in which technology is ubiquitous. Fleer (2017) has argued that technologies are changing the conditions for play, and, consistent with the concept of postdigital play (Jayemanne et al, 2016), the MakEY project indicated children's initiative, competence, and confidence with those technologies. Throughout the MakEY project, children moved across digital and nondigital domains in their play with materials.…”
Section: Postdigital Maker Playmentioning
confidence: 94%
See 2 more Smart Citations
“…Although play was significant for all early years settings that participated in the MakEY project, it was evident that the nature of play is changing in a world in which technology is ubiquitous. Fleer (2017) has argued that technologies are changing the conditions for play, and, consistent with the concept of postdigital play (Jayemanne et al, 2016), the MakEY project indicated children's initiative, competence, and confidence with those technologies. Throughout the MakEY project, children moved across digital and nondigital domains in their play with materials.…”
Section: Postdigital Maker Playmentioning
confidence: 94%
“…However, the nature of play has changed over the years, with technology playing an increasingly significant role (Marsh & Bishop, 2014). While various concepts have been developed to explain the nature of contemporary play in a digital landscape, such as connected play (Marsh, 2017), and ecology of play (Arnott, 2016), in this paper we draw on the concept of postdigital play (Jayemanne et al, 2016). As outlined in the work of Marsh and Arnott, among others, The term emphasizes the way in which the digital is so embedded in everyday play practices that it is no longer meaningful to consider the digital in contrast to nondigital.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, family members extended existing media interests across new media and non-media contexts. The ease with which family members steer their children's activities across digital and non-digital boundaries speaks to Jayemanne, Apperley, and Nansen's (2016) notion of the postdigital.…”
Section: Extendingmentioning
confidence: 99%
“…Studies suggest that early year engagement in makerspaces enables the development of individual agency, fosters social interaction and allows children to transition seamlessly across digital and non-digital domains in their maker play [182]. This final aspect has the potential to shape institutional pedagogical practices, coined in the literature as 'postdigital play' [183]. Whilst the focus of this review was restricted on play purely for enjoyment purposes, future research would benefit from trying to apply the strong concepts developed in it to research on makerspaces and postdigital play.…”
Section: Rq2 How Are These Affordances Delivered By Phygital Play Technologies?mentioning
confidence: 99%